PENEGAKAN HUKUM NOMOR 77 TAHUN 2016 TENTANG LAYANAN PINJAM MEMINJAM UANG BERBASIS TEKNOLOGI INFORMASI TERHADAP PERLINDUNGAN KONSUMEN - Sabrina Damanik, Eunike; Iriansyah, Iriansyah; Yusuf DM, M (Maleo Law Journal, 2022)
The development of the world in all fields makes changes in all aspects, one of which is in the field of fintech. The use of technology is increasingly prioritized to facilitate all human activities and needs. whose presence is now gaining popularity among the public because it is supported by the emergence of many startups or start-up companies that offer various digital services such as payments, investments, loans, and financing. The purpose of this study was to determine the analysis of aspects of law enforcement Number 77 of 2016 concerning Information Technology-Based Lending and Borrowing Services on Consumer Protection. Analyzing the legal consequences of default for consumers in online lending and what legal remedies can be taken based on a review of the Financial Services Authority Regulation Number 77 of 2016 concerning Information Technology-Based Lending and Borrowing Services. The method in this research is normative which discusses law enforcement against default consumers who use online loan services in terms of Law Number 77 of 2016 concerning Information Technology-Based Borrowing-Lending Services. The result of this research is that the regulation on Consumer Protection in the Financial Services Sector which is regulated in POJK Number 1/POJK.07/2013 has not been able to reach the peer to peer lending market because there are no rules stating that peer to peer lending. lending is included in consumer protection regulations for the service sector finance